2021
DOI: 10.1016/j.jspr.2021.101888
|View full text |Cite|
|
Sign up to set email alerts
|

Desiccant drying prior to hermetic storage extends viability and reduces bruchid (Callosobruchus chinensis L.) infestation of mung bean (Vigna radiata (L.) R. Wilczek) seeds

Abstract: Desiccant drying prior to hermetic storage extends viability and reduces bruchid (Callosobruchus chinensis L.) infestation of mung bean (Vigna radiata (L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
7
4
0
Order By: Relevance
“…The pod bead ratio of 1:1 was found more effective than other doses. The outcome of this study is also in line with the findings of Sultana et al [8] who reported that the green gram seeds stored in hermetic container with zeolite beads resulted in 9.00% pod damage whereas it was 9.33% in sodium aluminium silicate after 6 months of treatment. Similar type of result were found with Jyothsna [9], who revealed that the pods mixed with beads in 1:1 ratio was highly effective in reducing the damage caused by C. serratus after 3, 6 and 9 months of storage.…”
Section: Figure In the Parentheses Are Square Root Transformed Values...supporting
confidence: 92%
See 3 more Smart Citations
“…The pod bead ratio of 1:1 was found more effective than other doses. The outcome of this study is also in line with the findings of Sultana et al [8] who reported that the green gram seeds stored in hermetic container with zeolite beads resulted in 9.00% pod damage whereas it was 9.33% in sodium aluminium silicate after 6 months of treatment. Similar type of result were found with Jyothsna [9], who revealed that the pods mixed with beads in 1:1 ratio was highly effective in reducing the damage caused by C. serratus after 3, 6 and 9 months of storage.…”
Section: Figure In the Parentheses Are Square Root Transformed Values...supporting
confidence: 92%
“…Similar type of results were reported by Sultana et al [8] who observed that green gram seeds mixed with drying beads recorded the lowest oviposition (10 to13 eggs per10 g of seeds) by Callosobruchus chinensis after six months of storage. The seed moisture content was the primary factor limiting oviposition, rather than whether the storage container was hermetic.…”
Section: Efficacy Of Desiccant Beads On Fecundity Of C Serratussupporting
confidence: 89%
See 2 more Smart Citations
“…For use in planting, seeds will be stored such that an acceptable level of physiological quality (viability, vigor) will be maintained over the expected storage period. As a commodity, seeds (“grain” in the case of cereal seeds) will be stored to avoid losses due to, for example, insects, fungi and biochemical reactions (Mahapatra and Lan, 2007 ; Sultana et al, 2021 ; Ziegler et al, 2021 ). The actual storage conditions will depend on the expected storage period, i.e., how long the seeds need to be stored to meet demand before new seeds are produced.…”
Section: Introductionmentioning
confidence: 99%